Chronic NSAIDs Use Increases the Risk of a Second Hip Fracture in Patients After Hip Fracture Surgery. Issue 38 (September 2015) - Huang, Kuo-Chin; Huang, Tsan-Wen; Yang, Tien-Yu; Lee, Mel S.; Chebli., Caroline
<x xml:space="preserve">Abstract</x> Abstract Nonsteroidal anti-inflammatory drugs (NSAIDs) control musculoskeletal pain, but they also cause adverse side effects. The aim of this study is to explore the impact of chronic NSAIDs use on the risk of a second hip fracture (SHFx) after hip fracture surgery. This population-based case-cohort study used the Taiwan National Health Insurance Research Database (NHIRD), which contains data from >99% of the population. From a random sample of 1 million enrollees, we identified 34, 725 patients ≥40 years who sustained a first hip fracture and underwent hip fracture surgery between 1999 and 2009. Chronic NSAIDs use is defined as taking NSAIDs for at least 14 days a month for at least 3 months. The main outcome measure is an SHFx. Propensity-score matching was used to control for confounding. Our results revealed that chronic NSAIDs use was a significant risk factor for an SHFx in patients after hip fracture surgery and for adverse side effects that might last for 12 months. Compared with the nonchronic-use cohort (n = 29, 764), the adjusted hazard ratio of an SHFx was 2.15 (95% CI: 2.07–2.33) for the chronic-use cohort (n = 4961). The 10-year Kaplan–Meier survival analyses showed that chronic NSAIDs use presented a positive year-postsurgery-dependency effect on the risk of an SHFx in all the selected subgroups of patients (all P ⩽ 0.011). In conclusion, chronic NSAIDs use increases the risk of an SHFx after hip fracture surgery. Avoiding chronic NSAIDs use must be emphasized in clinical practice.